Più turismo con il GIS (GEOmedia, 2015)
In questa case history Virtualgeo presenta la sua soluzione per diffondere l'uso delle nuove tecnologie geomatiche a supporto del turismo grazie a un WebGIS ricco di funzionalità . La realizzazione di un percorso turistico digitale auspica di fornire possibili suggerimenti all'interno del processo di adeguamento tecnologico perseguito dalle municipalità .In this case study Virtualgeo presents its solution to spread the use of new geomatics technologies to support tourism through a webGIS that is rich of features. The creation of a tourist route through digital technology-based processing tools hopes to provide possible suggestions in the process of technological updating pursued by the municipalities of Eastern Venice, providing those simple solutions that become more and more "necessary" in an era constructed through the network. The created webGIS is a tourist product that is useful for the institutions directly concerned with the promotion of the territory; for the "natives", i.e. the citizens who often know little the area where they live, and for the eco-tourists visiting this wonderful land. The webGIS should not be neglected as an extraordinary tool of knowledge of the area (cultural heritage, landscape, environment) for teaching in schools of all levels.